Celebrating the 30th anniversary of the European Association of Neuro-Oncology - Preusser, Matthias; Platten, Michael; Short, Susan C. (Neuro-Oncology, 2024)
The European Association of Neuro-Oncology (EANO) was established by formal constitution in Brussels, Belgium, in 1994 by a group of European neuro-oncologists who saw the need to promote and professionalize Neuro-Oncology in Europe through a dedicated medical association. The first EANO Meeting was held in Maastricht, the Netherlands, in 1994, during which 180 of the participants established the society by formal election. Over the following decades, EANO evolved into an internationally leading, vibrant, interdisciplinary, and multiprofessional society representing the many faces of European Neuro-Oncology with a multitude of activities and projects aiming at advancing education, research, and care for patients affected by tumors of the nervous system. In 2019, EANO moved its place of registration from Brussels, Belgium, to Vienna, Austria. Today, EANO has over 700 members from more than 70 countries, both in Europe and abroad. EANO is well connected to national and international societies and proud to contribute to joint efforts to advance Neuro-Oncology worldwide in collaborations with the Society of Neuro-Oncology (SNO), the Asian Society of Neuro-Oncology (ASNO), the European Organization for Research and Treatment of Cancer (EORTC), and many other national and international medical and research organizations. This year, in 2024, we celebrate the 30th Anniversary of EANO. As Past President, Current President, and President-Elect of the society, we take the opportunity to reflect on the past, present, and future of EANO.